STUDENTSâ€™ ANXIETY IN LEARNING ENGLISH AT ENGLISH EDUCATION STUDY PROGRAM KHAIRUN UNIVERSITY - Andriani Abd. Rahman; Roswita M. Aboe; Naniek Jusnita (Cakrawala Bahasa, 2023)
The objective of this research was to investigate the factors contribute studentsâ€™ anxiety in leaning English and their strategies to reduce the anxiety. This research used qualitative descriptive method. The subject of the research were 40 students of the second semester of the English Language Education study Program Khairun University. The data were collected by using questionnaire and interview. The result of this research show that most of the students are at â€œAnxiousâ€ level students. There are 18 (45%) students who experience â€œAnxiousâ€ level, 10 (25%) students are in â€œMildly Anxiousâ€ level, 9 (22.5%) students are in â€œVery anxiousâ€™ level, 2 (5%) students are in â€œvery relaxedâ€, an the last 1 (2.5%) students are in â€œrelaxedâ€ level. Furthermore, there were three factors can cause anxiety based on FLCAS, which included communication apprehension (CA), test anxiety, and fear of negative evolution and there were five strategies that the students can use to minimize their anxiety which included preparation, relaxion, positive thingking, peer seeking, resignation.